CONNECTED SPEECH MODIFICATION AMONG INDONESIAN LISTENERS OF ENGLISH AND THE TEACHING - Darwanto, Agus (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
In spoken English, sound adjustments called connected speech modification (or post lexical processes), such as linking, palatalization, and deletion commonly occur in the stream of speech across word boundaries. The stretch of modified spoken English may pose challenges among the listeners to comprehend the message. Then, this article sees that connected speech modification is one of the problems among the Indonesian listeners of English in comprehending spoken English. It will also elaborate the probable problem areas. Suggestions for teaching to help solve the problems are to be provided at the end of this article.